2012 IEEE Symposium on Security and Privacy 2012
DOI: 10.1109/sp.2012.47
|View full text |Cite
|
Sign up to set email alerts
|

Third-Party Web Tracking: Policy and Technology

Abstract: In the early days of the web, content was designed and hosted by a single person, group, or organization. No longer. Webpages are increasingly composed of content from myriad unrelated "third-party" websites in the business of advertising, analytics, social networking, and more. Thirdparty services have tremendous value: they support free content and facilitate web innovation. But third-party services come at a privacy cost: researchers, civil society organizations, and policymakers have increasingly called at… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
296
0
1

Year Published

2013
2013
2019
2019

Publication Types

Select...
6
2
2

Relationship

1
9

Authors

Journals

citations
Cited by 372 publications
(300 citation statements)
references
References 32 publications
3
296
0
1
Order By: Relevance
“…‡ ‡ Prior work has demonstrated that the policy distinction between PII and non-PII is not based on sound science. Researchers have demonstrated "reidentification" risks in a number of applications, including health records (21,22), location histories (23)(24)(25), web search queries (26), web browsing activity (27)(28)(29), movie reviews (30), and social network graphs (31,32).…”
Section: Resultsmentioning
confidence: 99%
“…‡ ‡ Prior work has demonstrated that the policy distinction between PII and non-PII is not based on sound science. Researchers have demonstrated "reidentification" risks in a number of applications, including health records (21,22), location histories (23)(24)(25), web search queries (26), web browsing activity (27)(28)(29), movie reviews (30), and social network graphs (31,32).…”
Section: Resultsmentioning
confidence: 99%
“…For example, due to privacy concerns, much interest exists in determining how thirdparty data collection agencies use the information they collect. (See [51] for a survey.) Despite being a question of information flow, program analyses are inapplicable since the programs are unavailable, as in our setting.…”
Section: Resultsmentioning
confidence: 99%
“…4 In particular, using several different Facebook accounts with distinctly different user profiles, we install and accept the requested permissions for each of the 997 applications. To monitor the application behavior, we use a modified version of a Firefox plug-in [7], allowing us to record all the HTTP and HTTPS traffic. Similarly, we investigated each of the 377 working applications listed on the RenRen App center.…”
Section: Methodsmentioning
confidence: 99%